Visual C++ templates - Murray, William H. 1943- (Prentice Hall PTR Microsoft technollogy series, 2000)
Topics covered: Overview of the Standard C++ Library and the Standard Template Library (STL), STL history and features, STL reference, tutorial, sample code, template syntax, template functions and classes, namespaces, new casting operations, STL function objects, exception handling, STL support templates, algorithm and iterator reference and tutorial, vectors, stacks and queues, lists, maps, numeric support templates, sets and multisets, allocators, bitsets, C++ Standard Library header files reference, assertions, exceptions, types and strings, time functions, streams, and valarrays.